The Role of Media Framing as Watchdog for Forest and Land Fires in Indonesia - Sujoko, Anang; Fahira, Nabila Aulia (Universitas Muhammadiyah Ponorogo, 2022)
Media surveillance in forest and land fires in Riau during 2019 is essential in protecting the environment and enforcing environmental crimes perpetrators. Online media coverage, apart from having a vital obligation to disseminate information to the public and a form of control over the government. The purpose of this study was to determine how the framing used by Tirto.id was related to the coverage of forest and land fires in Riau in 2019. The news was analyzed using Robert Entman's framing analysis method. There are four elements used in this research, namely, define problems, diagnose causes, make moral judgments, and treatment recommendation. The results found were that Tirto.id tended to frame the arrest of suspects who caused forest and land fires in Riau in 2019 as defining problems. Then, Tirto.id framed that the forest and land fires in Riau in 2019 were a deliberate mistake by humans, that it was an easy and cheap method to extend the farm. The assessment given by Tirto.id is that the government has been negligent in overcoming environmental problems. Therefore, Tirto.id provides a solution in providing fair laws to the suspects of forest and land fires in Riau in 2019.